Efficacy of preoperative frailty assessment in patients with gastrointestinal disease. Issue 3 (27th January 2021) - Kameyama, Hitoshi; Sakata, Jun; Hanyu, Takaaki; Ichikawa, Hiroshi; Nakano, Masato; Nagahashi, Masayuki; Shimada, Yoshifumi; Kobayashi, Takashi; Wakai, Toshifumi
Abstract : Aim: The role of preoperative frailty assessment in patients with gastrointestinal (GI) disease remains unclear. This study aimed to clarify the relationship between frailty and postoperative outcomes in patients with GI disease. Methods: This study investigated 42 patients (aged ≥65 years) with GI disease who underwent abdominal surgery. The frailty status was analyzed using the Japanese version of the Cardiovascular Health Study criteria. We also investigated postoperative outcomes. Results: Of the 42 patients, seven (16.7%) were robust, 24 (57.1%) were prefrail and 11 (26.2%) were frail. Postoperative complications were observed in 45.5% and 63.6% of prefrail and frail patients, respectively, whereas no complications were found in robust patients ( P = 0.026). The median hospital stay was 15, 19.5 and 27 days in robust, prefrail and frail patients, respectively ( P  < 0.01). Conclusion: Preoperative frailty status based on the Japanese version of the Cardiovascular Health Study criteria is associated with postoperative complication incidence and hospital stay extension in patients with GI disease. Geriatr Gerontol Int 2021; : – .